2009
DOI: 10.1089/fpd.2009.0325
|View full text |Cite
|
Sign up to set email alerts
|

Anisakis pegreffi Etiological Agent of Gastric Infections in Two Italian Women

Abstract: Two cases of gastric anisakiasis have been documented in two Italian women who had consumed raw anchovies (Engraulis encrasicolus). The first patient was a 49-year-old woman presenting with epigastric pain and bloody vomiting after ingestion of marinated (vinegar) raw anchovies. During the esophagogastroduodenoscopy (EGDS) a white color worm was detected and extracted from cardia by means of biopsy forceps. The second patient was a 59-year-old woman with irritable bowel syndrome and gastritis, who underwent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 17 publications
1
50
0
1
Order By: Relevance
“…Clinical signs depend on the site where the larva is deposited, but it generally causes abdominal pain and vomiting, as well as some allergic reactions (Fumarola et al, 2009;Valls et al, 2005). Nematodes of the Hysterothylacium genus reach sexual maturity inside the intestine of fish or marine mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical signs depend on the site where the larva is deposited, but it generally causes abdominal pain and vomiting, as well as some allergic reactions (Fumarola et al, 2009;Valls et al, 2005). Nematodes of the Hysterothylacium genus reach sexual maturity inside the intestine of fish or marine mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Although this illness can be caused by other anisakids, the main etiological agent of this parasitosis is considered to be Anisakis simplex s.s. [1,2]. In Italy, however, it has been attributed to Anisakis pegreffii [3][4][5] . It is not yet known whether these two species are equally pathogenic, but trials performed on laboratory animals indicate that Anisakis simplex penetrates the mucous membrane of the digestive tract to a greater proportion [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Japan is undoubtedly the most affected country (Ishikura et al, 1993;Kim et al, 2013), but human cases are also reported in Italy, Spain, United States and China (Fumarola et al, 2009;Kojima et al, 2013;Qin et al, 2013;Ramanan et al, 2013;Valle et al, 2012).…”
Section: Introductionmentioning
confidence: 99%